Trans-peritectic steel slab casting powder as well as preparation method and application thereof
By using the cross-clad steel slab protection slag, and using specific raw material components and spray methods to prepare hollow particles, the problem of uneven heat transfer in medium carbon steel and slab shells is solved, and horizontal heat transfer is effectively controlled, avoiding longitudinal cracks and bonded steel leakage, and improving the quality of casting billets.
Patent Information
- Application Number
- CN202510023616.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
AI Technical Summary
The heat transfer of the blank shells of medium carbon steel and crystalline steel is uneven, resulting in obvious longitudinal cracks of the cast blank and the problem of bonding and leakage of steel.
A trans-enclosed steel slab protection slag is used to prepare hollow particles, including wollastonite, slag powder, fluorite, limestone, ice crystal, bauxite, soda ash, manganese carbonate, medium carbon graphite, earth-like graphite, carbon black and binder, and the hollow particles are prepared by spraying method to control horizontal heat transfer.
Effectively control horizontal heat transfer, avoid longitudinal cracks and bonded steel leakage, and improve the quality and pass rate of the cast billet.
Smart Images

Figure CN119702986A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgical auxiliary materials, and specifically discloses a trans-peritectic steel slab protective slag and a preparation method and application thereof. Background Art
[0002] In response to market demand and site conditions, steel mills need a protective slag that can meet the needs of both medium carbon steel and peritectic steel in slabs. The universal protective slag needs to meet on-site use and the qualified rate of casting billets reaches 99.3%. The role and characteristics of this protective slag are mainly to meet the continuous casting needs of medium carbon steel in slabs and the normal use of molten steel in the peritectic area.
[0003] Due to the solidification characteristics of medium carbon steel and peritectic steel, especially after the peritectic reaction occurs, when the copper wall of the meniscus water-cooled crystallizer provides a large degree of supercooling, the liquid first crystallizes solid δFe and grows in the form of dendrites; when the liquid temperature is lower than 1495℃, the peritectic reaction δFe+L→γFe occurs, and a γFe cladding is formed around the δFe dendrites, forming a three-phase interface of δFe+L+γFe; the temperature continues to drop, and the γFe phase diffuses and grows on the phase interface through carbon atoms, continuously consuming the δFe phase and the liquid phase until it is completely converted into the γFe phase. The local heat transfer of the billet shell of this steel is prone to uneven, resulting in obvious longitudinal cracks in the billet and even bonding and steel leakage.
[0004] Based on this, the research and development of a protective slag material with excellent heat transfer performance is of great significance to the development of medium carbon steel and peritectic steel. Summary of the invention
[0005] In view of the problem in the prior art that the shell of medium carbon steel and peritectic steel is prone to uneven heat transfer, resulting in obvious longitudinal cracks in the cast billet, the present invention provides a cross-peritectic steel slab protective slag and its preparation method and application. The cross-peritectic steel slab protective slag can not only effectively control horizontal heat transfer and meet the use requirements of medium carbon steel and peritectic steel slabs, but also avoid the problems of longitudinal cracks and bonding leakage in the continuous casting process.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: The first aspect of the present invention provides a trans-peritectic steel slab protective slag, which includes the following raw material components in percentage by mass: 38%-42% wollastonite, 8%-12% slag powder, 10%-14% fluorite, 7%-10% limestone, 5%-7% cryolite, 3%-6% bauxite, 5%-10% soda ash, 3%-5% manganese carbonate, 1%-3% medium carbon graphite, 1%-3% earthy graphite, 1%-3% carbon black and 1%-3% binder.
[0007] Controlling the heat transfer in the horizontal direction can effectively solve the problems of longitudinal cracks and bonding leakage that appear in the continuous casting process. Because the heat transfer of the protective slag is uneven, the shrinkage of different parts of the solidified shell is inconsistent, which will generate thermal stress inside the ingot, resulting in cracks on the surface or inside of the ingot, reducing the quality of the ingot. The present invention selects soda ash, sodium fluoride, cryolite and manganese carbonate as composite fluxes, which can effectively avoid the slag film from generating high thermal resistance, prevent excessive heat flow from causing thermal stress concentration, and play an effect of controlling the heat transfer of the slag film. In particular, the addition of manganese carbonate can replace part of the soda ash, which not only has the effect of reducing the melting temperature, but also has the effect of coloring the slag film, which has a positive effect on controlling the heat transfer of the slag film. The addition of slag powder can replace part of the limestone, reduce the total amount of carbonate, and thus make the melting state more stable. Bauxite can adjust the melting point and viscosity of the protective slag, improve the phase equilibrium and crystallization performance of the protective slag, maintain the temperature of the molten steel stable during the continuous casting process, reduce the temperature fluctuation of the surface of the ingot, and then reduce the generation of cracks on the surface of the ingot. Cryolite can improve the fluidity of the protective slag, help optimize the viscosity of the protective slag, make the protective slag have good fluidity in the liquid state, can better fill the gap between the crystallizer wall and the ingot, reduce the friction between the ingot and the crystallizer wall, and thus improve the surface quality of the ingot. The present invention can effectively control the growth rate and size of the crystal by controlling the content of each raw material component of the protective slag, thereby avoiding the phenomenon of longitudinal cracks and bonding leakage during the continuous casting process.
[0008] Preferably, the basicity of the trans-peritectic steel slab protection slag is 1.24-1.26.
[0009] Considering the need to control heat transfer and meet the requirements of use on medium carbon and peritectic steel slabs, the present invention designs a basic mold slag, namely CaO / SiO 2 >1.0. The inventors have found through a large number of creative experiments that the protective slag with acidic alkalinity has no obvious turning temperature during the temperature drop process, and the slag film of the protective slag is glassy. Although it has good lubrication properties, its heat transfer control ability is relatively poor. However, as the temperature drops, the alkaline protective slag first precipitates lanceolite. When the temperature drops to about 1250°C, albite, calcium feldspar and pseudo-wollastonite begin to precipitate, but the precipitation amount is very small. Magnesium feldspar precipitates the fastest until about 1150°C, when the mineral phases almost no longer precipitate.
[0010] Preferably, the viscosity of the transperitectic steel slab protection slag at a melting point of 1120-1170° C. is 0.09 Pa·S-0.11 Pa·S.
[0011] Preferably, the transperitectic steel slab protection slag comprises the following chemical components in percentage by mass: SiO 2 :25%-30%, CaO: 30%-35%, Al 2 O 3:4%-7%, Na 2 O: 5%-7%, MnO: 2%-4%, F - : 7%-11%, Tc: 5%-8%, the balance is inevitable impurities.
[0012] Preferably, the binder is any one of dextrin, pregelatinized starch or sodium carboxymethyl cellulose.
[0013] Preferably, the trans-peritectic steel slab protection slag is a hollow granular ball with a particle size of 0.1mm-1.5mm.
[0014] Hollow ball protection slag has the advantages of good thermal insulation performance and good spreadability on the molten steel surface.
[0015] A second aspect of the present invention provides a method for preparing a transperitectic steel slab mold slag, comprising the following steps: Step 1: weigh all raw material components except the binder according to the designed ratio, crush and sieve them, and mix them evenly to obtain a mixed material; Step 2: adding a binder and water to the mixed material, mixing evenly, and obtaining a mixed slurry with a mass concentration of 55wt%-65wt%; Step three, granulating the mixed slurry by spraying method, sieving, and obtaining transperitectic steel slab protective slag.
[0016] Preferably, in step 1, the mesh number of the sieve used for screening is 300 mesh, and the mass proportion of the material under the sieve is ≥96%.
[0017] Preferably, in step three, the pressure of the spray granulation is 14MPa-18MPa.
[0018] Preferably, in step three, the spray granulation is carried out in a high-temperature spray tower, the temperature in the high-temperature spray tower is 730°C-780°C, and the air outlet temperature of the high-temperature spray tower is 140°C-150°C.
[0019] Preferably, in step three, the sieving uses a sieve with a mesh size of 10 mesh and 60 mesh.
[0020] A third aspect of the present invention provides an application of the trans-peritectic steel slab protective slag or the trans-peritectic steel slab protective slag prepared by the trans-peritectic steel slab protective slag preparation method in the field of steel smelting. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a turning curve diagram of the protective slag of the trans-peritectic steel slab obtained in Example 1; Figure 2 This is a turning curve diagram of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 1; Figure 3This is a turning curve diagram of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 2; Figure 4 This is a turning curve diagram of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 3; Figure 5 It is a comparison diagram of the porcelain pieces after the melting of the protective slag of the trans-peritectic steel slab obtained in Example 1 and Comparative Examples 1-3; wherein, a is a picture of the porcelain piece after the melting of the protective slag of the trans-peritectic steel slab obtained in Example 1; b is a picture of the porcelain piece after the melting of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 1; c is a picture of the porcelain piece after the melting of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 2; d is a picture of the porcelain piece after the melting of the protective slag of the trans-peritectic steel slab obtained in Comparative Example 3. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1 This embodiment provides a protective slag for a transperitectic steel slab, the specific contents of which are as follows: The cross-peritectic steel slab protection slag is prepared from the following raw materials in percentage by weight: 42% wollastonite, 10% slag powder, 12% fluorite, 6% limestone, 6% cryolite, 5% bauxite, 8% industrial sodium carbonate, 4% manganese carbonate, 2% medium carbon graphite, 1.5% earthy graphite, 2% carbon black and 1.5% dextrin; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 75 minutes, and control the mass concentration of the slurry to 60wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 16MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C and the air outlet temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 60-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0024] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 :26.57%,CaO:33.50%,Al 2 O 3:6.76%,Na 2 O: 5.98%, MnO: 2.43%, F - : 8.28%, Tc: 7.24% and 9.24% impurities, basicity is 1.26, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0025] Example 2 This embodiment provides a protective slag for a transperitectic steel slab, the specific contents of which are as follows: The cross-peritectic steel slab protection slag is prepared from the following raw materials in percentage by weight: 46% wollastonite, 10% slag powder, 12.5% fluorite, 5% limestone, 5% cryolite, 2% bauxite, 8.5% sodium carbonate, 4% manganese carbonate, 2% medium carbon graphite, 1.5% earthy graphite, 2% carbon black and 1.5% dextrin; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 70 minutes, and control the mass concentration of the slurry to 65wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 18MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C, and the outlet air temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 60-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0026] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 : 28.27%, CaO: 34.97%, Al 2 O 3 :4.27%,Na 2 O: 6.05%, MnO: 2.43%, F - : 8.05%, Tc: 7.18% and 8.78% impurities, basicity is 1.24, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0027] Example 3 This embodiment provides a protective slag for a transperitectic steel slab, the specific contents of which are as follows: The cross-peritectic steel slab protection slag is made of the following raw materials in percentage by weight: 43% wollastonite, 10% slag powder, 11% fluorite, 7% limestone, 4% cryolite, 5% bauxite, 7% industrial sodium carbonate, 4% manganese carbonate, 2% medium carbon graphite, 1.5% earthy graphite, 2% carbon black and 1.5% dextrin; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 65 minutes, and control the mass concentration of the slurry to 55wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 14MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C, and the air outlet temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 60-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0028] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 :27.10%,CaO:33.78%,Al 2 O 3 :6.06%,Na 2 O: 5.53%, MnO: 2.43%, F - : 7.38%, Tc: 7.25% and 10.47% impurities, basicity is 1.25, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0029] Comparative Example 1 This comparative example provides a cross-peritectic steel slab protection slag, the specific contents are as follows: The cross-peritectic steel slab protection slag is prepared from the following raw materials in percentage by weight: 56% wollastonite, 13% fluorite, 3% sodium fluoride, 6% bauxite, 11% industrial sodium carbonate, 4% silica, 2% medium carbon graphite, 1.5% earthy graphite, 2% carbon black and 1.5% dextrin; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 75 minutes, and control the mass concentration of the slurry to 60wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 16MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C and the air outlet temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 60-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0030] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 : 33.91%, CaO: 32.22%, Al 2 O 3 :5.04%,Na 2 O: 7.97%, F - : 7.12%, Tc: 6.85% and 6.89% impurities, basicity is 0.95, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0031] Comparative Example 2 This comparative example provides a cross-peritectic steel slab protection slag, the specific contents are as follows: The cross-peritectic steel slab protection slag is made of the following raw materials in percentage by weight: 40% wollastonite, 3% medium carbon graphite, 2.5% earthy graphite, 15% industrial soda ash, 17% fluorite, 4% sodium fluoride, 6% limestone, 9% bauxite, 2% carbon black and 1.5% dextrin; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 75 minutes, and control the mass concentration of the slurry to 60wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 16MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C and the air outlet temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 60-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0032] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 : 22.2%, CaO: 31.37%, Al 2 O 3 :7.09%,Na 2 O: 10.82%, F -: 9.35%, Tc: 9.76% and 9.41% impurities, basicity is 1.41, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0033] Comparative Example 3 This comparative example provides a cross-peritectic steel slab protection slag, the specific contents are as follows: The cross-peritectic steel slab protection slag is prepared from the following raw materials in percentage by weight: wollastonite 26%, fluorite 14%, medium carbon graphite 2%, earthy graphite 1.5%, industrial soda ash 10%, cryolite 10%, bauxite 5%, limestone 16%, silica 12%, carbon black 2% and dextrin 1.5%; The specific preparation process of the cross-peritectic steel slab protection slag is as follows: Step 1: weigh all raw material components except the binder according to the designed ratio, crush them, pass through a 300-mesh sieve, and then put them into a vertical mixing tank in increasing order of specific gravity, mix them evenly, and obtain a mixed material; Step 2: Add a binder to the mixed material, add water and stir for 75 minutes, and control the mass concentration of the slurry to 60wt% to obtain a mixed slurry; Step three, pressurize the mixed slurry to 16MPa through a plunger pump, and pump it into a high-temperature spray tower for granulation. Set the temperature in the spray tower to 730°C and the air outlet temperature of the spray tower to 150°C. Sieve the protective slag after spray granulation through 10-mesh and 130-mesh sieves to obtain the protective slag for trans-peritectic steel slab.
[0034] Through the use of F5 fluorine detector, atomic absorption and titration instruments, it can be seen that the composition of the obtained transperitonic steel slab protection slag includes: SiO 2 : 26.19%, CaO: 28.88%, Al 2 O 3 :7.94%,Na 2 O: 7.91%, F - : 10.77%, Tc: 8.66% and 9.65% impurities, basicity is 1.10, the morphology is hollow granular balls, and the particle size is 0.1mm-1.5mm.
[0035] Test example The samples obtained in each embodiment and comparative example were tested for melting point using RDS-05 fully automatic slag melting point and melting rate tester, and the viscosity (1300°C) and turning curve were tested using RTW-10 melt property comprehensive tester. The results are shown in Table 1 and Figure 1-4 As shown: Table 1 Test results of the mold slag obtained in each embodiment and comparative example
[0036] according to Figure 1-4It can be seen that in the temperature-drop viscosity curve of the trans-peritectic steel slab protective slag provided in Example 1, the turning curve is relatively smooth and the turning temperature is moderate; in the temperature-drop viscosity curve of the trans-peritectic steel slab protective slag provided in Comparative Example 1, no obvious turning temperature can be seen, and cracks are easily formed on the surface of the ingot; the melting point viscosity of the trans-peritectic steel slab protective slag provided in Comparative Example 2 basically reaches the desired index, but the turning angle of the temperature-drop viscosity curve is too large, and under certain circumstances, a large amount of crystals are easily precipitated, causing production accidents; the turning angle of the turning curve provided in Comparative Example 3 is too large, and the turning curve is not smooth enough, and the melting state is unstable.
[0037] from Figure 5 It can be seen that after the cross-peritectic steel slab protective slag provided in Example 1 is melted, there are basically no holes on the porcelain piece. This may be because the addition of manganese carbonate replaces part of the industrial soda ash, and the addition of slag powder replaces part of the limestone, which reduces the total amount of carbonate and makes the melting state more stable. At the same time, it can be seen from the color that the color of the cross-peritectic steel slab protective slag obtained in Example 1 is dark black, which also shows that the coloring ability of manganese carbonate is obvious. After coloring the slag film, it has a positive effect on controlling the heat transfer of the slag film. The color of the cross-peritectic steel slab protective slag obtained in Example 1 is light yellow after melting, indicating that the slag film is not colored; the color of the cross-peritectic steel slab protective slag obtained in Example 2 is brownish yellow after melting, but holes appear on the porcelain piece; the color of the cross-peritectic steel slab protective slag obtained in Example 3 is brownish yellow after melting, and large bubble-like holes appear on the porcelain piece, indicating that the protective slag may cause an unstable effect on the melting state. This is because during the melting process, carbonates are constantly decomposed by heat, and carbon dioxide and its oxides are produced first. Carbon dioxide, as a gas, will destroy the slag layer structure when produced in large quantities, causing uneven melting phenomena such as separate melting and agglomeration.
[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A protective slag for a transperitectic steel slab, characterized in that: The cross-peritectic steel slab protection slag includes the following raw material components in percentage by weight: wollastonite 38%-42%, slag powder 8%-12%, fluorite 10%-14%, limestone 7%-10%, cryolite: 5%-7%, bauxite 3%-6%, soda ash 5%-10%, manganese carbonate 3%-5%, medium carbon graphite 1%-3%, earthy graphite 1%-3%, carbon black 1%-3% and binder 1%-3%.
2. The protective slag for transperitectic steel slab according to claim 1, characterized in that: The basicity of the trans-peritectic steel slab protection slag is 1.24-1.
26.
3. The protective slag for trans-peritectic steel slab according to claim 1, characterized in that: The viscosity of the trans-peritectic steel slab protection slag at a melting point of 1120° C.-1170° C. is 0.09 Pa·S-0.11 Pa·S.
4. The cross-peritectic steel slab protection slag according to claim 1, characterized in that: The cross-peritectic steel slab protection slag includes the following chemical components in percentage by weight: SiO2: 25%-30%, CaO: 30%-35%, Al2O3: 4%-7%, Na2O: 5%-7%, MnO: 2%-4%, F - : 7%-11%, Tc: 5%-8%, the balance is inevitable impurities.
5. The cross-peritectic steel slab protection slag according to claim 1, characterized in that: The binder is any one of dextrin, pregelatinized starch or sodium carboxymethyl cellulose.
6. The protective slag for transperitectic steel slab according to claim 1, characterized in that: The trans-peritectic steel slab protection slag is a hollow granular ball with a particle size of 0.1mm-1.5mm.
7. A method for preparing a transperitectic steel slab mold slag according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: weigh all raw material components except the binder according to the designed ratio, crush and sieve them, and mix them evenly to obtain a mixed material; Step 2: adding a binder and water to the mixed material, mixing evenly, and obtaining a mixed slurry with a mass concentration of 53wt%-63wt%; Step three, granulating the mixed slurry by high temperature spraying method, sieving, and obtaining transperitectic steel slab protective slag.
8. The method for preparing the protective slag for the transperitectic steel slab according to claim 7, characterized in that: In step 1, the mesh number of the sieve used for sieving is 300 mesh, and the mass ratio of the material under the sieve is ≥ 96%; and / or In step 3, the granulation pressure is 14MPa-18MPa.
9. The method for preparing the protective slag for the transperitectic steel slab according to claim 7, characterized in that: In step three, the granulation is carried out in a high-temperature spray tower, the temperature in the high-temperature spray tower is 730°C-780°C, and the outlet air temperature of the high-temperature spray tower is 140°C-150°C.
10. Application of the transperitectic steel slab protection slag as described in any one of claims 1 to 6 or the transperitectic steel slab protection slag prepared by the method for preparing the transperitectic steel slab protection slag as described in any one of claims 7 to 9 in the field of steel smelting.